Extraction and preconcentration of the highly lipophilic antioxidant 2,6-Diisobornyl-4-Methylphenol and its metabolite from plasma samples for the determination by HPLC-MS/MS - Lakeev, Alexander P.; Yanovskaya, Elena A.; Yanovsky, Vyacheslav A.; Andropov, Mikhail O. (Journal of analytical chemistry)
A procedure is proposed for the extraction of 2,6-diisobornyl-4-methylphenol (IBP), the molecule with potential multi-target activity, and its active metabolite 2,6-diisobornyl-4-hydroxymethylphenol (IBP-OH) from human and rat plasma samples for further determination by liquid chromatography-tandem mass spectrometry. The solubility of IBP (in mg/mL) in various organic solvents is determined. In particular, the compound is readily soluble in chloroform (346 ± 14), methyl tert-butyl ether (98.6 ± 3.8), and ethyl acetate (96.8 ± 2.0). It is shown that the use of a mixture of chloroform and isopropanol (5 : 1, v/v) as an extraction system with simultaneous protein precipitation makes it possible to extract only 66 ± 10% of IBP, while the recovery of IBP-OH is 96 ± 7%. Pre-dilution of 200 µL of plasma with 300 µL saline increases IBP recovery to 100 ± 4%. Drying the extracts in a vacuum concentrator (air, 45°C) with the further reconstitution of the residues in 300 μL of acetonitrile facilitates the purification of biosamples and the preconcentration of analytes. The total sample preparation time does not exceed 70 min, and the duration of an analysis is 7 min, the injection volume is 2 µL. The procedure has been successfully tested on actual rat plasma samples after a single oral administration of IBP (10 mg/kg in oil) in the framework of pharmacokinetic studies.